Synergistic Analgesic Effects of Ginger, Colchicum, and Nux Vomica Extracts in a Unani Polyherbal Combination - Syed Shariq Mian, Mohd Shuaib, Azmat Zehra, Mo Suheb Ansari, Iqbal Husain, Bushra Begam, Mohammad Asif (South Eastern European Journal of Public Health, 2025)
Ginger, colchicum, and detoxified nux vomica extracts are combined in an effective dose ratio to evaluate analgesic activity. This combination has not been previously utilized by Unani practitioners. Three unprocessed herbs (Ginger, Colchicum, and Nux vomica) were separated using hydro-alcoholic (50-50%) and aqueous solvents. Every extract, including aqueous and hydro-alcoholic extracts, had its established LD50. To create aqueous and hydro-alcoholic dosage forms, the corresponding extracts were now combined in an efficient dosage ratio. Analgesic effectiveness of both formulations (aqueous and hydro-alcoholic) is assessed using Eddy's hot plate test, analgesiometer test, and formalin test. The reference drug diclofenac sodium was used to examine the effectiveness. The groups administered either the standard dose or the test drug had the highest increase in reaction time at 120 minutes in Eddy's hot plate test. The degree of significance was p<0.001 with a larger dose of aqueous extract (1100 mg/kg), therefore maximum tolerance of pain was observed. The combination containing the larger dose of hydro-alcoholic extract (580 mg/kg) had the longest reaction time (4.97 seconds) on the analgesiometer at 75 minutes. The flinches at 14.81 seconds in the formalin test were considerably lessened by the larger dose of the aqueous extract (1100 mg/kg) than by the lower dose (P<0.05). In summary, our research validates the analgesic properties of polyherbal extracts combination. As a result, when used together, these medications have the potential to effectively treat acute, subacute, and chronic nociception. Thus, suitable dosage formulations for the treatment of algesia may be created in the future.